2014
DOI: 10.1158/1078-0432.ccr-13-0839
|View full text |Cite
|
Sign up to set email alerts
|

Cabozantinib Inhibits Prostate Cancer Growth and Prevents Tumor-Induced Bone Lesions

Abstract: Purpose Cabozantinib, an orally available multi-tyrosine kinase inhibitor with activity against MET and vascular endothelial growth factor receptor 2 (VEGFR2), induces resolution of bone scan lesions in men with castration-resistant prostate cancer bone metastases. The purpose of this study was to determine whether cabozantinib elicited a direct anti-tumor effect, an indirect effect through modulating bone, or both. Experimental Design Using human prostate cancer xenograft studies in mice we determined caboz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 34 publications
6
58
1
1
Order By: Relevance
“…It has been reported that cabozantinib suppressed cell migration and invasion in various types of tumor cells (23,35). Consistently, our results showed that cabozantinib inhibited HGF-stimulated migration and invasion in HCC cell lines.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that cabozantinib suppressed cell migration and invasion in various types of tumor cells (23,35). Consistently, our results showed that cabozantinib inhibited HGF-stimulated migration and invasion in HCC cell lines.…”
Section: Discussionsupporting
confidence: 90%
“…While 5 out 11 patients with prior VEGF inhibitor therapies achieved a partial response, all 3 patients without prior anti-VEGF treatment had a partial response. In agreement with prior results in prostate cancer, cabozantinib showed meaningful activity in osteoblastic bone lesions supporting the preclinical relevance of MET and VEGF in regulating osteoblast function [92]. Adverse events profile was consistent with prior studies with cabozantinib and included grade 3 diarrhea (20%), hypertension (13%), decreased appetite (13%), and fatigue (7%).…”
Section: Multikinase Inhibitorssupporting
confidence: 89%
“…Both the MET and VEGF signaling pathways appear to be important for regulating the function of osteoblasts and osteoclasts, which are two key cell types in the bone microenvironment that are involved in the development of metastatic bone lesions (28). In nonclinical studies, cabozantinib blocked progression of both osteoblastic and osteolytic lesions in prostate cancer xenografts in bone (29)(30)(31). In this study, activity of cabozantinib on existing bone lesions was observed.…”
Section: Discussionmentioning
confidence: 57%